2019
DOI: 10.1039/c9ra04170b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in direct trifluoromethylation of olefinic C–H bonds

Abstract: The aim of this review is to provide a comprehensive overview of the direct trifluoromethylation of olefinic C–H bonds with special attention on the mechanistic aspects of the reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…A few of them are concentrated on specific areas such as Umemoto's reagent [21], reactions in aqueous media [31], hypervalent iodine reagents [32], CF 3 -S transfer agents [33] and photolytic reactions [34]. Further, a few reviews have been discussed fluorine effect on chemical reactions [35] and in some reviews, it is described some selective trifluoromethylated reactions [36][37][38][39]. Although, a good number of review articles are available, sometimes it is difficult to extract important ideas from the vast amount of discussion.…”
Section: Aim Of the Reviewmentioning
confidence: 99%
“…A few of them are concentrated on specific areas such as Umemoto's reagent [21], reactions in aqueous media [31], hypervalent iodine reagents [32], CF 3 -S transfer agents [33] and photolytic reactions [34]. Further, a few reviews have been discussed fluorine effect on chemical reactions [35] and in some reviews, it is described some selective trifluoromethylated reactions [36][37][38][39]. Although, a good number of review articles are available, sometimes it is difficult to extract important ideas from the vast amount of discussion.…”
Section: Aim Of the Reviewmentioning
confidence: 99%
“…Trifluoromethyl (CF 3 )-containing organic compounds do not exist in natural products . The development of efficient synthetic methodologies for the incorporation of the CF 3 group into organic molecules has received more attention in recent years . Owing to its unique physical, chemical, and biological properties, the CF 3 group can substantially alter an organic molecule’s lipophilicity, metabolic stability, and ability to cross the blood–brain barrier; trifluoromethylated compounds have found wide applications in the fields of medical, pharmaceutical, agricultural, and material sciences …”
Section: Introductionmentioning
confidence: 99%
“…Although significant advancements in this field have been made in the direct introduction of the CF 3 group into organic moieties, such as nucleophilic, electrophilic, and free radical reactions, the methods for the synthesis of functionalized α-trifluoromethylated carboxylic acid esters are still relatively limited. In addition, α-trifluoromethylated carboxylic acids have been identified as bioactive compounds and versatile intermediates in synthetic chemistry. To this end, a few elegant works showed that the synthesis of α-CF 3 esters could be achieved by the reaction of ester derivatives, α-diazo esters, and sensitive ketene silyl acetals with Togni’s reagent and Umemoto’s reagent, , CF 3 I and TMSCF 3 (Scheme a).…”
Section: Introductionmentioning
confidence: 99%
“…Fluoroalkylation of unactivated alkenes constitutes one of the most efficient and versatile strategies for synthesizing high-value fluorinated molecules. , Being among the most abundant chemical feedstocks in organic synthesis, simple alkenes are readily available in large quantities at low costs, and their characteristic reactivity profile enables a wide range of functionalization for constructing carbon–carbon and carbon–heteroatom bonds . In this regard, direct trifluoromethylation of unactivated alkenes allows the introduction of the smallest perfluoroalkyl group, CF 3 , into organic molecules with high efficiency, selectivity, and atom economy . For instance, the challenging allylic Csp 3 –CF 3 bond formation has been achieved by elegant copper-catalyzed trifluoromethylation of unactivated alkenes 1 (Scheme a) .…”
mentioning
confidence: 99%